A point-wise normalization method for development of biofidelity response corridors. Issue 15 (26th November 2015) - Gayzik, F.S.; Marcus, I.P.; Danelson, K.A.; Rupp, J.D.; Bass, C.R.; Yoganandan, N.; Zhang, J.
Abstract: An updated technique to develop biofidelity response corridors (BRCs) is presented. BRCs provide a representative range of time-dependent responses from multiple experimental tests of a parameter from multiple biological surrogates (often cadaveric). The study describes an approach for BRC development based on previous research, but that includes two key modifications for application to impact and accelerative loading. First, signal alignment conducted prior to calculation of the BRC considers only the loading portion of the signal, as opposed to the full time history. Second, a point-wise normalization (PWN) technique is introduced to calculate correlation coefficients between signals. The PWN equally weighs all time points within the loading portion of the signals and as such, bypasses aspects of the response that are not controlled by the experimentalist such as internal dynamics of the specimen, and interaction with surrounding structures. An application of the method is presented using previously-published thoracic loading data from 8 lateral sled PMHS tests conducted at 8.9 m/s. Using this method, the mean signals showed a peak lateral load of 8.48 kN and peak chest acceleration of 86.0 g which were similar to previously-published research (8.93 kN and 100.0 g respectively). The peaks occurred at similar times in the current and previous studies, but were delayed an average of 2.1 ms in the updated method. The mean time shifts calculated with the method ranged from 7.5% to 9.5% of the event. The method may be of use in traditional injury biomechanics studies and emerging work on non-horizontal accelerative loading.